The preferential binding of histone H1 to DNA scaffold-associated regions is determined by its C-terminal domain. - Roque, A.; Orrego, M.; Ponte, I.; Suau, P. (Nucleic Acids Research, 2004)
Histone H1 preferentially binds and aggregates scaffold-associated regions (SARs) via the numerous homopolymeric oligo(dA).oligo(dT) tracts present within these sequences. Here we show that the mammalian somatic subtypes H1a,b,c,d,e and H1 degrees and the male germline-specific subtype H1t, all preferentially bind to the Drosophila histone SAR. Experiments with the isolated domains show that whilst the C-terminal domain maintains strong and preferential binding, the N-terminal and globular domains show weak binding and poor specificity for the SAR. The preferential binding of SAR by the H1 molecule thus appears to be determined by its highly basic C-terminal domain. Salmine, a typical fish protamine, which could have its evolutionary origin in histone H1, also shows preferential binding to the SAR. The interaction of distamycin, a minor groove binder with high affinity for homopolymeric oligo(dA).oligo(dT) tracts, abolishes preferential binding of the C-terminal domain of histone H1 and protamine to the SAR, suggesting the involvement of the DNA minor groove in the interaction.